Low-resolution spectroscopy of the chromospherically active stars 61 Cyg AB with small telescopes - Pokhvala, S.M.; Zhilyaev, B.E.; Reshetnyk, V.M.; Shavlovskij, V.I. (Advances in Astronomy and Space Physics, 2014)
We carried out high-speed low-resolution spectroscopy of two stars, 61 Cyg A and B with small telescopes. They are known as chromospherically active stars of the K5V (A) and K7V (B) spectral types. These two stars are supposed to have high-powered chromospheres. Spectroscopic monitoring of both stars showed variations of intensity in the Balmer lines and the Mg b triplets at time intervals ranging from seconds to several minutes. From the spectrum data one can find that relative variations in the Hα, Hβ lines and the Mg b triplets are about 1% and the relative power of chromospheric activity about 2 · 10⁻⁴.